E-wallet di Kalangan Mahasiswa : Apakah Literasi Keuangan Digital dan Persepsi Keamanan Menjadi Faktor Penentu - Delia Nurfadhilah; Iis Aisyah; Sri Hardianti Sartika (Journal of Islamic Economics and Finance, 2025)
Service users e-wallet face a number of issues, including a lack of knowledge about digital finance as well as concerns about security and trust in services e-wallet. This problem is supported by the phenomenon of many educators being trapped in loans online. The focus of this research is on the influence of digital financial literacy and security perceptions on service adoption e-wallet among students with the UTAUT approach. Quantitative research method with survey data collection using a questionnaire totaling 35 statements, consisting of 12 statements on the digital financial literacy variable, 13 statements on the security perception variable and the service adoption variable. e-wallet as many as 10 statements. The respondents for this research involved 224 students (25% men, 75% women) majoring in Economic Education, class of 2021-2024. The data analysis technique uses multiple linear regression analysis using the SPSS version 25 application. The research results show that the variables of digital financial literacy and security perceptions have a positive and significant effect on service adoption e-wallet simultaneously and partially. It is hoped that this research can contribute useful thoughts and information and can enrich knowledge and economic development as well as become reference material for further research.